Immunotherapeutic Potential of Lactobacillus Species as Immune Checkpoint Inhibitors in Cancer Immunotherapy - Renukadevi J; Sam Helinto J; Prena D (Journal of Bio-X Research)
Recent research has shown that probiotics, particularly Lactobacillus sp., have potential as modulators of the immune system. This review explores the immunotherapeutic potential of Lactobacillus species via adjuvant therapy with immune checkpoint inhibitors (ICIs), such as programmed cell death protein-1, programmed death ligand-1, and cytotoxic T-lymphocyte antigen-4 inhibitors, which have revolutionized cancer treatment by enhancing T-cell-mediated antitumor immunity. However, patient response remains questionable, prompting further study into the role of the gut microbiota in modulating these therapies. These probiotics influence immune responses through interactions with immune cells such as dendritic cells, macrophages, and T cells. These interactions promote cytokine production, enhance CD8+ T-cell activity, and improve the gut barrier. Specific Lactobacillus strains can increase ICI efficacy through the production of proinflammatory cytokines and associated side effects. Optimizing Lactobacillus-based therapies and integrating them with existing cancer treatments may lead to improved patient outcomes. Although the formulation of probiotic species in advanced drug delivery systems, such as niosomes and liposomes, may prove to be successful, regulatory guidelines need to be followed to support their nontoxic effects in preclinical trials followed by clinical studies. Although the concomitant administration of probiotics with ICIs remains a promising strategy, the underlying mechanisms need to be explored to support their systemic nontoxic effects.